Profit dynamics across the largest euro area countries and sectors - Laurent Maurin; Moreno Roma; Igor Vetlov (European Central Bank (ECB), 2011)
This paper explores the behavior of profits in the four largest euro area countries (Germany, France, Italy and Spain) and the euro area as a whole, while at the same time considering three main sectors (manufacturing, construction and services) in each economy over the period 1988–2010. The paper presents stylized facts about profit developments and, applying a vector autoregressive modeling framework, discusses the sensitivity of profits to four distinctive structural shocks (a demand shock, an employment shock, a wage and price mark-up shocks). In addition, it provides the shock decomposition of historical developments in profits across countries and sectors.
Keywords: C32; E23; E25; 330; historical decomposition; Impulse responses; Profits; sectoral determinants; VARs